The yin and yang of B cells in a constant state of battle: intestinal inflammation and inflammatory bowel disease - Zogorean, Roxana; Wirtz, Stefan (Frontiers in Immunology, 2023)
Inflammatory bowel disease (IBD) is a chronic inflammatory disease of the gastrointestinal tract, defined by a clinical relapse-remitting course. Affecting people worldwide, the origin of IBD is still undefined, arising as a consequence of the interaction between genes, environment, and microbiota. Although the root cause is difficult to identify, data clearly indicate that dysbiosis and pathogenic microbial taxa are connected with the establishment and clinical course of IBD. The composition of the microbiota is shaped by plasma cell IgA secretion and binding, while cytokines such as IL10 or IFN- are important fine-tuners of the immune response in the gastrointestinal environment. B cells may also influence the course of inflammation by promoting either an anti-inflammatory or a pro-inflammatory milieu. Here, we discuss IgA-producing B regulatory cells as an anti-inflammatory factor in intestinal inflammation. Moreover, we specify the context of IgA and IgG as players that can potentially participate in mucosal inflammation. Finally, we discuss the role of B cells in mouse infection models where IL10, IgA, or IgG contribute to the outcome of the infection.